Helicobacter pylori and Hyperuricemia: Revisiting Gout Diagnosis in Young Adults with Normal Renal Function - Abdullah M Nasrat; Salwa AM Nasrat; Randa M Nasrat; Mohammad M Nasrat; Sana Y Babiker (Medical Science: Trends and Innovations Vol. 4, 2025)
Gout is a very old disease which existed for thousands of years with joint swelling, pain or tenderness; the first description of symptoms of gout was found in the Egyptian medical papyri dating to 3000 years BC. The study aimed to illustrate that the detection of high levels of serum uric acid in young adults with perfect kidney function should not be considered the final diagnosis of hyperuricemic pre-gouty illness. Gout is a very old disease which existed for thousands of years with joint swelling, pain or tenderness. Hyperuricema has long been established as the major etiologic factor in gout. Gout has recently become the most common presentation of arthritis in developed countries. Hyperuricemia increases the risk of gout and is also a risk factor for cardiovascular diseases. Hyperuricemia could contribute to diabetes, hypertension and arteriosclerosis due to endothelial dysfunction triggered by vascular wall tissue inflammation because of urate crystal deposition. These reasons are sufficient to render physicians anxious in the immediate assessment and treatment of elevated serum uric acid levels. On the contrary, patients hesitate to accept the decision of their pre-gouty illness due to elevation of serum urate particularly if they are young and have perfect renal function. H. pylori could migrate or get forced to migrate to the colon leading to colonic re-absorptive error with excess accumulation of fluids and salts in the body; uric acid could be among these reabsorbed elements giving a picture of elevated serum uric acid levels that would have no relation to age of the individual or the integrity of his renal function. Furthermore, gout has been recently considered as one of the auto-inflammatory diseases, hence cytokines are the most common mediators of inflammation; therefore, the role played by the increased mucosal production of inflammatory mediators (cytokines) induced by H. pylori is supposed to contribute to the pathogenesis of gout. In this situation, hyperuricemia is not expected to be adequately or successfully improved by traditional urate-lowering measures regardless of the age of the patient or the state of his kidney function. Thirty-three patients aged between 31-40 years, having normal kidney function and a frank history of H. pylori dyspepsia were included in the study due to newly discovered elevated levels of serum uric acid regardless of their body built or any associated. The existence of colonic H. pylori strains was proved by the H. pylori fecal antigen test. All patients underwent colon clear employing the potent natural senna purge once and colon care was maintained by vinegar-mixed food therapy for one week. Serum uric acid levels dropped to normal within 3 days after the colon cleared in 30 patients while the remaining 3 patients showed the same drop at the end of the first week of natural therapy. Detection of high levels of uric acid in young adults should not be considered as a final diagnosis of pre-gouty illness unless kidney function is assessed, and the association of H. pylori is excluded by specific tests. Revision of the guidelines for the diagnosis and treatment of H. pylori and many chronic diseases associated with it may be needed.